2000
DOI: 10.1172/jci7798
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-1 regulation of connexin43 in cardiac myocytes

Abstract: Gap junction channels composed of connexin43 (Cx43) are essential for normal heart formation and function. We studied the potential role of the Wnt family of secreted polypeptides as regulators of Cx43 expression and gap junction channel function in dissociated myocytes and intact hearts. Neonatal rat cardiomyocytes responded to Li + , which mimics Wnt signaling, by accumulating the effector protein β-catenin and by inducing Cx43 mRNA and protein markedly. Induction of Cx43 expression was also observed in card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
236
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(262 citation statements)
references
References 51 publications
23
236
0
1
Order By: Relevance
“…Cx43 localization is regulated through a variety of mechanisms, including protein trafficking following translation and overall stabilization of intercalated discs. Recently the role of Wnt in expression of Cx43 has been established (24,49). Consistently, we confirmed that Wnt inhibitor reversed up-regulation of Cx43 level and cell-cell coupling in Cdon-knockdown neonatal cardiomyocytes.…”
Section: Discussionsupporting
confidence: 86%
“…Cx43 localization is regulated through a variety of mechanisms, including protein trafficking following translation and overall stabilization of intercalated discs. Recently the role of Wnt in expression of Cx43 has been established (24,49). Consistently, we confirmed that Wnt inhibitor reversed up-regulation of Cx43 level and cell-cell coupling in Cdon-knockdown neonatal cardiomyocytes.…”
Section: Discussionsupporting
confidence: 86%
“…Alternatively, the presence of low levels of ZO-1 at the edge of Cx43-GFP plaques could result indirectly via macromolecular associations between GJs and other cell-cell junctions that incorporate ZO-1. Adherens junctions are logical candidates in this respect as they are known to play a pivotal role in GJ stability (Hertig et al 1996;Jongen et al 1991;Li et al 2005;Meyer et al 1992;Musil et al 1990;Wei et al 2005) and cadherin-associated catenin complexes have been shown to bind both Cx43 (Ai et al 2000;Wei et al 2005) and ZO-1 (Itoh et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, other genes that may be affected by Wnt-1 signaling and were observed in the data set produced by the GIP-dependent AIMAH microarray analysis included the gap junction gene connexin43, a molecule that is also induced by Wnt-dependent increase of b-catenin in cardiomyocytes (Ai et al, 2000) (data not shown).…”
Section: Discussionmentioning
confidence: 99%